Blue Concept Economy Implementation in Coastal Communities Based on The Law Number 11 of 2020 on Job Creation Perspective - M. Afif Hasbullah (Journal of Social Science, 2022)
This study aims to analyze the application of the blue economy concept to coastal communities based on the Law Number 11 of 2020 concerning Job Creation perspective. This study is a qualitative empirical legal research (juridical sociological) with a conceptual approach. The data taken rom legal materials used include primary legal materials such as statutory regulations and secondary legal materials such as books, journals, and mass media articles. The results show the application of blue economy model and Indonesia's development planning has a positive impact on the fisheries, marine resources and the environment sustainability. However, the approach in the Job Creation Law has the potential to hinder sustainable development realization and blue economy development, as illustrated in several changes to the Law of Job Creation